CRITICAL DISCOURSE ANALYSIS ON KOMPAS.COM NEWS: 'GERAKAN #2019GANTIPRESIDEN' - Hendri Pitrio Putra; Sulis Triyono (Leksema: Jurnal Bahasa dan Sastra, 2018)
This article is a result of critical discourse analysis (CDA) to the news entitled Gerakan #2019GantiPresiden di Antara Ambiguitas Hukum dan Syahwat Politik at Kompas.com. The approach employed in this research is the three-dimensional CDA developed by Norman Fairclough. The purposes of this research are to describe the micro, mezzo, and macro as well as the social, political and cultural situation from the linguistic aspects in Gerakan #2019GantiPresiden di Antara Ambiguitas Hukum dan Syahwat Politik text. The results show that there are linguistic aspects in the form of diction in the direct sentences that are used by Kompas.com with the theme #2019GantiPresiden. This movement is considered as a constitutional movement indicated as a rebellion because it is supported by political interests towards their current government rival. This is closely related to the background of Kompas.com as a pro-government online mass media. It is also acceptable if Kompas.com creates a positive image of the current government. The main point of information that is conveyed in the news of #2019GantiPresiden is that this movement possibly threats the government of Jokowi Widodo who will run again for the presidential election in 2019.